Reversible holographic 3D data storage in oxide glasses using visible lasers - Nalin, Marcelo [UNESP]; Carvalho, E. J.; Cescato, L.; Poirier, G. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (My University, 2006)
Antimony based glasses have been investigated for the first time regarding the possibility of holographic data storage using visible lasers sources. Changes in both refractive index and the absorption coefficient were measured using a holographic setup. The modulation of the optical constants is reversible by heat treatment. Bragg gratings were written under visible light of an Ar laser and erased thermally.